PENGARUH DIRECT INSTRUCTION BERBANTUAN STRATEGI MODELING THE WAY TERHADAP RESPON DAN HASIL BELAJAR MATERI HIDROKARBON - Syafitri, Windi; Harun, A.Ifriany; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis aims of this study were to determine whether there was a significant different of student achievement, determine how much influence of direct instruction models assisted by modelling the way strategy toward student achievement, determine the correlation between response and student achievement of experiment class and control class. This study used quasy experimental research with pretest-posttest non-equivalent control group design. The sample of this research were X B as experimental class which taught using direct instruction models through modelling the way strategy and X C as control class wich taught using conventional method. Achievement test, questionnaire response, observasion sheet and interview guidelines ware used as the research instrument. According to independent-t test toward student achievement data, there was no significant difference of student achievement between those clasess (Asym.sig.(2-tailed) of 0,342). Learning using direct instruction models through modelling the way strategy gave 14,80% effect on improving student achievemen influenced by teacher. According to Person Correlation, there was no correlation between response and student achievement of control class (Sig.(2-tailed) of 0,306). According to Kendallâ€™s Correlation, there was no correlation between response and student achievement of experiment class (Sig.(2-tailed) of 0.398).Â Keyword: Direct Instruction, Modeling The Way, Hydrocarbon.